Impacts of trait anxiety on visual working memory, as a function of task demand and situational stress. Issue 1 (2nd January 2021) - Spalding, David M.; Obonsawin, Marc; Eynon, Caitie; Glass, Andrew; Holton, Lindsay; McGibbon, Monica; McMorrow, Calhoun L.; Nicholls, Louise A. Brown
ABSTRACT: Higher trait anxiety can impair cognitive functioning via attention, but relatively little is known about the impacts on visual working memory. These were investigated using previously validated visual feature binding tasks. In Study 1, participants' memory for visual features (shapes) and feature bindings (coloured shapes) was assessed. Stimulus presentation was simultaneous or sequential, varying attentional demand, and participants were grouped according to trait cognitive anxiety (low, moderate, high). No reliable effect of trait anxiety, either cognitive or somatic, was found on memory accuracy, but moderate trait cognitive anxiety was associated with faster correct response times (i.e. increased efficiency) when stimuli were sequentially presented. In Study 2, the role of situational stress was explored during a simultaneously presented task. Higher trait cognitive and somatic anxiety were both associated with poorer efficiency during both shape and binding memory tasks. Trait somatic anxiety also predicted poorer binding effectiveness (i.e. accuracy), in those reporting higher state cognitive anxiety. Situational stress predicted binding effectiveness, but never interacted with trait anxiety, and was therefore not necessary to observe these trait anxiety-visual working memory relationships. Trait cognitive and somatic anxiety, and situational stress, therefore each influence visual working memory performance.